2021
DOI: 10.4103/bc.bc_57_20
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and stroke severity: Impact of clinical risk factors

Abstract: BACKGROUND: Specific clinical and demographic risk factors may be associated with improving or worsening neurologic outcomes within a population of acute ischemic stroke (AIS) patients with a history of obstructive sleep apnea (OSA). The objective of this study was to determine the changes in neurologic outcome during a 14-day recovery as it relates to initial stroke severity in AIS patients with OSA. METHODS: This retrospective study analyzed baseline clinical risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In a study by Yaggi et al conducted on 1022 adults with no history of stroke or myocardial infarction, the risk of stroke was shown to increase as the severity of OSA increased [ 134 ]. This result was verified in further follow-up studies and meta-analyses, where adults with OSA showed approximately a two-fold higher risk of stroke [ 135 , 136 , 137 , 138 , 139 ]. Additionally, untreated OSA after acute stroke increases long-term mortality and neurological outcomes [ 125 , 126 ], which highlights the importance of rapid treatment of post-stroke OSA.…”
Section: Associations Between the Factors Influencing Cognitive Decli...mentioning
confidence: 52%
“…In a study by Yaggi et al conducted on 1022 adults with no history of stroke or myocardial infarction, the risk of stroke was shown to increase as the severity of OSA increased [ 134 ]. This result was verified in further follow-up studies and meta-analyses, where adults with OSA showed approximately a two-fold higher risk of stroke [ 135 , 136 , 137 , 138 , 139 ]. Additionally, untreated OSA after acute stroke increases long-term mortality and neurological outcomes [ 125 , 126 ], which highlights the importance of rapid treatment of post-stroke OSA.…”
Section: Associations Between the Factors Influencing Cognitive Decli...mentioning
confidence: 52%
“…We observed that AIS patients with a history of hypertension and elevated measured diastolic pressure after initial stroke were associated with increased stroke severity. Hypertension is associated with an increased risk of initial stroke and the control of hypertension reduces this risk [ 21 , 58 , 59 ]. Randomized control trials have continuously challenged the “lower, the better” hypothesis for hypertension [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, women are more likely to present with comorbidities of atrial fibrillation [25] and hypertension [26], whereas men are more likely to present with congestive heart disease and diabetes [27]. While existing studies [25][26][27] reveal evidence of a gender difference in stroke symptoms, past clinical history and comorbidities in the non-telestroke setting, how these may contribute to stroke severity and possible gender difference in the telestroke setting is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, women are more likely to present with comorbidities of atrial fibrillation [25] and hypertension [26], whereas men are more likely to present with congestive heart disease and diabetes [27]. While existing studies [25][26][27] reveal evidence of a gender difference in stroke symptoms, past clinical history and comorbidities in the non-telestroke setting, how these may contribute to stroke severity and possible gender difference in the telestroke setting is not fully understood. A significant benefit of the telestroke network is that it provides a high quality of acute stroke care, including diagnostic procedures, management of stroke comorbidities, and access to allied health assessments than in control hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation